2020
DOI: 10.5194/bg-17-963-2020
|View full text |Cite
|
Sign up to set email alerts
|

Basal thermal regime affects the biogeochemistry of subglacial systems

Abstract: Abstract. Ice formed in the subglacial environment can contain some of the highest concentrations of solutes, nutrients, and microbes found in glacier systems, which can be released to downstream freshwater and marine ecosystems and glacier forefields. Despite the potential ecological importance of basal ice, our understanding of its spatial and temporal biogeochemical variability remains limited. We hypothesize that the basal thermal regime of glaciers is a dominant control on subglacial biogeochemistry becau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 89 publications
5
17
0
Order By: Relevance
“…The marine humic-like component H2 has also previously been found in basal ice from Devon Island (Dubnick et al, 2017), Greenland (Kellerman et al, 2020;Pain et al, 2020), and Alaska marine DOM (Walker et al, 2009). The protein-like glacier DOM found in meltwater runoff draining Sverdrup Glacier and the humic-like marine DOM found in the surrounding coastal ocean is consistent with previous findings, indicating that glaciers are microbially based ecosystems capable of supplying comparatively labile DOM to downstream environments (Dubnick et al, 2020;Hood et al, 2009). In the ocean, labile glacial DOM will likely promote secondary productivity, with bacteria and microzooplankton using it as a carbon source.…”
Section: Nutrient and Carbon Export In Glacial Meltwater Runoff To The Surface Oceansupporting
confidence: 88%
See 4 more Smart Citations
“…The marine humic-like component H2 has also previously been found in basal ice from Devon Island (Dubnick et al, 2017), Greenland (Kellerman et al, 2020;Pain et al, 2020), and Alaska marine DOM (Walker et al, 2009). The protein-like glacier DOM found in meltwater runoff draining Sverdrup Glacier and the humic-like marine DOM found in the surrounding coastal ocean is consistent with previous findings, indicating that glaciers are microbially based ecosystems capable of supplying comparatively labile DOM to downstream environments (Dubnick et al, 2020;Hood et al, 2009). In the ocean, labile glacial DOM will likely promote secondary productivity, with bacteria and microzooplankton using it as a carbon source.…”
Section: Nutrient and Carbon Export In Glacial Meltwater Runoff To The Surface Oceansupporting
confidence: 88%
“…The elevated ammonium concentrations observed here may also indicate microbial degradation of glacial DOM (Kumar et al, 2016) and/or may be partially sourced from rock weathering in the subglacial environment (Holloway & Dahlgren, 2002). A recent study by Dubnick et al (2020) corroborates this, having found abundant and distinct microbial communities in surface and basal ice at Sverdrup Glacier. The humic-like component H1 has been found in both marine and terrestrial studies (Coble, 2007;De Souza Sierra et al, 1994;Stedmon et al, 2003) and has been previously observed in basal ice from numerous glaciers on Devon Island (Dubnick et al, 2017).…”
Section: Nutrient and Carbon Export In Glacial Meltwater Runoff To The Surface Oceansupporting
confidence: 81%
See 3 more Smart Citations